Transpulmonary B-type natriuretic peptide uptake and cyclic guanosine monophosphate release in heart failure and pulmonary hypertension: the effects of sildenafil - Melenovsky, Vojtech; Al-Hiti, Hikmet; Kazdova, Ludmila; Jabor, Antonin; Syrovatka, Petr; Malek, Ivan; Kettner, Jiri; Kautzner, Josef (Journal of the American College of Cardiology, 2009)
OBJECTIVES: We sought to identify factors that discriminate heart failure (HF) patients with normal and elevated pulmonary vascular resistance (PVR) and to elucidate the role of cyclic guanosine monophosphate (cGMP)-dependent vasodilation. BACKGROUND: Mechanisms of PVR increase in patients with chronic HF are incompletely understood. METHODS: Twenty-two HF patients with high pulmonary vascular resistance (H-PVR) (>200 dyn.s.cm(-5)) were compared with 24 matched low pulmonary vascular resistance (L-PVR) patients of similar age, sex, body size, HF severity, and volume status who were undergoing invasive hemodynamic study. Pulmonary arterial (PA) and venous blood samples from a wedged PA catheter were used to calculate transpulmonary B-type natriuretic peptide (BNP) uptake and cGMP release. The H-PVR patients were re-examined 1 h after a 40-mg oral dose of sildenafil. RESULTS: Although transpulmonary BNP uptake was similar (p = 0.2), cGMP release was diminished in the H-PVR patients (-1.9 vs. 27.8 nmol.min(-1); p = 0.005). Transpulmonary BNP uptake and cGMP release correlated in the L-PVR patients (R = 0.6, p = 0.004) but not in the H-PVR. The H-PVR patients also had lower PA compliance, systemic arterial compliance (by 47% and 20%, p < 0.001 and p < 0.03), and cardiac index. Sildenafil reduced PVR (-47%), systemic resistance (-24%) and heart rate (-8%), increased cardiac index (+24%), and PA compliance (+87%, all p < 0.001), with a parallel increase of cGMP release (from -5.6 to 16.5 nmol.min(-1), p = 0.047), without affecting BNP uptake or norepinephrine(PA). The PVR response was not dependent on PA wedge pressure or pulmonary hypertension reversibility with prostaglandin E(1). CONCLUSIONS: The H-PVR patients have stiffening of both pulmonary and systemic arteries, preserved transpulmonary BNP uptake, but diminished cGMP release, which is reversible by the administration of sildenafil. This study provides in vivo evidence that phosphodiesterase 5A inhibition restores sensitivity of pulmonary vasculature to endogenous cGMP-dependent vasodilators.
Keywords: sildenafil citrát; arteria pulmonalis; kyselina 5'-guanylová; Middle Aged; mužské pohlaví; sulfony; Adult; Vasodilation; Sulfones; Guanosine Monophosphate; cévní rezistence; Pulmonary Artery; 3',5'-Cyclic-GMP Phosphodiesterases; ženské pohlaví; Humans; Hemodynamics; vazodilatancia; hemodynamika; Vasodilator Agents; Piperazines; vazodilatace; lidé středního věku; srdeční selhání; puriny; Natriuretic Peptide, Brain; Purines; Sildenafil Citrate; 3',5'-cyklické GMP-fosfodiesterasy; Vascular Resistance; dospělí; natriuretický peptid typu B; piperaziny; Female; Heart Failure; lidé; Male